Influence of color and height of pan traps to capture braconids (Hymenoptera: Braconidae) - Mena-Mociño, Laura Verónica; Pineda-Guillermo, Samuel; Martínez-Castillo, Ana Mabel; Gómez-Ramos, Benjamín; Lobit, Philippe Christian; Ponce-Saavedra, Javier; Figueroa-De La Rosa, José Isaac (Revista Colombiana de Entomología, 2016)
The aim of this study was to determine the effectiveness of capturing braconids (Hymenoptera: Braconidae) on yellow, blue, cream, and green pan traps at two heights (0 and 90 cm) for a period of four weeks in the Natural Protected Area “Cerro Punhuato”, (Morelia, Michoacan, Mexico). The reflectance of each color was measured with a field analytical spectrophotometer. One hundred four (104) specimens, belonging to 14 subfamilies and 28 genera, were collected. Yellow and green pan traps caught the largest number of specimens and the greatest diversity of genera, showing 56.5 % similarity, as estimated with the Bray-Curtis index. Yellow pan traps installed at ground level exceeded the capture in green pan traps. The level of reflectance of the green and yellow pan traps was in the range from 360 to 530 nm, possibly indicating that this is the wavelength range in which braconids are attracted to both colors.